PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN STEK STEVIA (Stevia rebaudiana B.) - Natalia Sumanto; Albert Sembiring (Universitas Muhammadiyah Mataram, 2021)
Stevia (Stevia rebaudiana R.) is a shrub that is widely used as a natural sweetener. Stevia is a natural sweetener that contains stevioside and rebaudioside A that is 300 times higher, not carcinogenic, and low in calories as a sweet taste than cane sugar. This value is a chance to make stevia sugar as a cane sugar companion. The aim of this study is to measure the effect of growing media on stevia cuttings' growth. This test was undertaken by randomized complete block design (RBD) with 6 treatments and 3 replications in the PoliteknikWBI Practice Laboratory. In order to assess the effect of each treatment. The data obtained were analyzed using analysis of variance at P<5%. The results of the research indicated that the mixed media of humus soil and litter compost (P4) provided the highest values for the observed parameters; the height of the stevia cuttings was 49.50 cm, had 222.76 leaves, the fresh leaf weight was 24.98 g, the total of fresh weight and dry weight was 49. 72 g and 21.70 g, respectively. From the results of this study, it can be concluded that the suitable planting medium for stevia propagation using shoot cuttings is a mixture of humus soil and litter compost with a ratio of 1: 1.